2020
DOI: 10.1038/s41586-020-2608-y
|View full text |Cite|
|
Sign up to set email alerts
|

ChAdOx1 nCoV-19 vaccine prevents SARS-CoV-2 pneumonia in rhesus macaques

Abstract: This is a PDF file of a peer-reviewed paper that has been accepted for publication. Although unedited, the content has been subjected to preliminary formatting. Nature is providing this early version of the typeset paper as a service to our authors and readers. The text and figures will undergo copyediting and a proof review before the paper is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers apply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
780
3
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 857 publications
(834 citation statements)
references
References 19 publications
36
780
3
15
Order By: Relevance
“…Although non-human primates represent an attractive model for SARS-CoV-2 vaccine development [2][3][4][5] , multiple studies [26][27][28] including our own suggest that the Syrian hamster provides an effective animal model to evaluate SARS-CoV-2 vaccine e cacy for the following reasons: 1) low dose (i.e. 10 2 -10 3 TCID 50 ) i.n.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although non-human primates represent an attractive model for SARS-CoV-2 vaccine development [2][3][4][5] , multiple studies [26][27][28] including our own suggest that the Syrian hamster provides an effective animal model to evaluate SARS-CoV-2 vaccine e cacy for the following reasons: 1) low dose (i.e. 10 2 -10 3 TCID 50 ) i.n.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the humoral immune response, type 1 biased S-speci c T cell immunity likely contributes to protection in convalescent COVID-19 patients 25 . Broadly-reactive and/or type 1 cytokine producing T cell responses are also characteristic of DNA, Adenovirus serotype 26 and chimpanzee Adenovirus vaccines that protected non-human primates against SARS-CoV-2 challenge and are in clinical development 2,4,5 . In vivo and in vitro T cell analyses in our study demonstrated that MF59C.1-adjuvanted Sclamp vaccination elicited a robust, broad and type 1 biased polyfunctional T cell response in mice, consistent with features of a T cell response that could contribute to protection against SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With extensive pulmonary surface area exposed to SARS- Consequently, in parallel to the in vivo studies described above, antibody engineering of clone AvGn-B has been performed and a panel of more potent variants has now been isolated. As shown in Table 2 Future studies will explore the efficacy of the AvGn-B and/or its variants in non-human primate models, several of which have been described for use in SARS-CoV-2 pathogenesis and countermeasure development studies 40,60,61 . Larger studies will also be conducted to examine whether AvGn-B and/or its variants by reducing viral load and accumulation of macrophages within the lung will prevent downstream inflammatory and coagulation sequalae of SARS-CoV-2 infection within other parenchymatous organs, particularly heart, kidneys and liver.…”
Section: Analysis Of Macrophage Infiltration In Lung Tissue Of Animalmentioning
confidence: 99%
“…and is more distantly related to the human infectious alphacoronaviruses HCoV 229E and HCoV NL63 (6). Finding ways to control and prevent further infection are top priorities which include the targeted discovery of drugs that impair viral mechanisms (7)(8)(9) and antigenic epitopes through which vaccines raise immunity (10)(11)(12). This study addresses both by utilizing evolutionary information from SARS-CoV-2 sequence and structural data to search for actionable functional sites for each protein in the SARS-CoV-2 genome.…”
Section: Introductionmentioning
confidence: 99%